Penerapan Model Cooperative Integrated Reading and Composition (CIRC) dalam Pembelajaran Keterampilan Menulis Teks Deskripsi pada Peserta Didik Kelas VII SMP Negeri 5 Pati Tahun Pelajaran 2022/2023 - Reni Ulfiana Wulandari; Mukhlis Mukhlis; Arisul Ulumuddin (Pusat Riset dan Inovasi Nasional, 2023)
This research was conducted due to the inaccuracy of SMP Negeri 5 Pati educators in using the learning model used in learning descriptive text writing skills. The application of the lecture-based Discovery Learning model has a negative effect on students becoming inactive and having difficulty describing an object quickly. The learning outcomes obtained by students were also unsatisfactory. Seeing this situation, I am encouraged to seek the application of other learning models to support the success of learning descriptive text writing skills for class VII students of SMP Negeri 5 Pati. The learning model used is the Cooperative Integrated Reading and Composition model. The data collection method applied is a qualitative method. This research was in class VII B SMP Negeri 5 Pati with a total of 32 students. Data collection techniques applied are test techniques and non-test techniques. From the research conducted, it is explained that learning the skills of writing descriptive text with the Cooperative Integrated Reading and Composition model can make it easier for students to describe or describe objects quickly. From the research data, the highest score was 86 - 100 (very good) for 24 students and 76 - 85 for 8 students.